Contract through online intermediary platforms - Cuena Casas, Matilde (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Online intermediary platforms have become major players in the development of the digital marketplace and raise important regulatory challenges. Technological progress This article focus on the analysis of platforms which are information society service providers and act as intermediaries (also in the material sense) enabling transactions between all kind of platform users: consumers (peer to peer, P2P, Consumer to Consumer, C2C) or entrepreneurs (Business to Business, B2B). A complex contractual relationship is generated: the contract concluded by the users with the platform that allows them access in order to achieve the interaction and, subsequently, the contract concluded between the users. The purpose of this paper is to diagnose and propose solutions to problems arising from contracting through online intermediary platforms. We have new operators who do not exactly fit into the models regulated in e-commerce legislation, which poses problems in determining their responsibility for the transactions carried out by users through the platforms. The “horizontality” of the legal relationships between peers in a multilateral market that creates regulatory challenges. The Community acquis on consumer protection is based on a chain distribution model: manufacturer, wholesaler, retailer and consumer on a vertical scale. The imbalance between the positions of the parties when the entrepreneur is a supplier and the purchaser a consumer (B2C), served as a justification for the design of a contractual system of consumer protection, typical of mass contracting. The economics of the platform makes this scheme obsolete because goods and services are exchanged between peers and individuals act as suppliers (prosumers). And in this case, what’s the weak part to protect? The first part of the paper analyses the phenomenon of recruitment through online intermediary platforms, traditionally linked to the so-called “collaborative economy”. After the necessary conceptual clarifications, the general characteristics are listed, at the same time as the problems that this contracting modality causes are diagnosed. Online reputation systems and the problems caused by false reviews, custom pricing are some of the topics discussed. The second part of the article analyses the problems that the triangular structure of this kind of way of contract. It analyses the relationship between users and the platform operator, the rights and obligations of the parties, as well as contracts between users among themselves to which the platform operator is not a party, but is actively involved. The paper concludes with proposals for legal reform to promote transparency in this type of contract and clarify the liability regime of the platform operator.